ASSESSMENT OF SUITABILITY OF RADIONAVIGATION DEVICES USED IN AIR - Henryk JAFERNIK; Kamil KRASUSKI; Jan MICHTA (Scientific Journal of Silesian University of Technology. Series Transport)
The article characterises/describes the radionavigation devices recommended for and used in contemporary aviation taking into account the requirements of the legal regulations concerning CNS/ATM systems as determined by international aviation organisations. The latest achievements in the field of satelite techniques connected with the development in electronic and information engineering as well as in the area of computing machines have resulted in the higher precision of determining the parameters of technical devices, therefore the article focuses especially on the issues of the application of satelite navigation for aviation and the possibility of its improvement.